DESIGNING HALOGEN BONDS FOR ENZYMATIC CATALYSTS - Mendez, Cesar Gustavo, author; Ho, P. Shing, advisor; Rappé, Anthony, committee member; Snow, Chris, committee member; Schauer, Grant, committee member (Colorado State University. Libraries, 2026)
Protein engineering is the process of modifying proteins to enhance functions or create new activities. Genetic code expansion (GCE) provides strategies to introduce new functional groups through site-specific incorporation of synthetic noncanonical amino acids. This makes it possible to introduce chemical groups not found in natural proteins and to test how these groups influence structure, function, and catalysis. In this thesis, GCE will be used to site-specifically introduce synthetic halogenated amino acids for the purposes of bond breaking and bond making in DNA processing enzymes.Halogen bonds are non-covalent interactions that involve the electron-deficient σ-hole of a covalently bound halogen atom. These interactions are widely used in the pharmaceutical industry, but their application in enzyme engineering is relatively underexplored. This thesis investigates whether synthetic halogenated amino acids can be utilized at active sites and how halogenation might affect the activity of an enzymatic catalyst. Creating new catalysts and studying their mechanisms contribute to the body of enzymatic knowledge and will help engineer the next generation of synthetic enzymes. The following work shows that halogenated amino acids can be used in enzyme active sites to tune activity and the catalytic mechanism.
Keywords: Halogen; DNA; Protein